An experimental study on parabolic trough solar cookers with materials collector of chrome stickers and glass mirrors - Amin, Muhammad; Rizal, Teuku Azuar; Amir, Fazri; Abdullah, Nasruddin A; Ginting, Suma Fachruri (Jurnal Polimesin, 2023)
Cooking, a fundamental human necessity, frequently relies on environmentally harmful energy sources. Concentrated solar power offers a promising solution through solar cookers to address this issue. This study assesses a Parabolic Trough Collector (PTC) solar cooker's performance with two reflector materials: chrome stickers and glass mirrors. The PTC-type solar cooker comprises essential components, including an absorber tube, a flexible conduit, and a spiral-shaped cooking container holder that accommodates a diverse range of cooking vessels. In the configuration of the PTC collector, reflectors fabricated from chrome stickers and glass mirrors are strategically employed to harness and concentrate solar radiation effectively. The absorber tube, crafted from copper, is filled with a heat-transfer fluid consisting of soya oil. Experimental investigations were conducted in a two-stage process, encompassing trials without any applied load and subsequently with varying loads. In the no-load experiments, alterations were made to the PTC collector's inclination angle, spanning the ranges of 15º, 20º, 25º, and 30º. In contrast, the load-bearing tests encompassed the assessment of the PTC solar cooker's performance under a diverse array of cooking scenarios, including boiling water, heating oil, frying eggs, and crisping crackers. The evaluated parameters encompassed key metrics such as incident solar radiation (Ir), ambient temperature (Ta), receiver temperature (Tr), fluid temperature (Tf), spiral furnace temperature (Tsf), and load temperature (To). Subsequently, the outcomes of the experiments were employed to determine the efficiency of the solar cooker. Analysis of the no-load test results indicates that the most favorable performance, as observed in the parameters Tr, Tf, and Tsf, is achieved at a collector inclination angle of 15º for both chrome sticker and glass mirror reflector materials. The solar cooker demonstrated commendable proficiency in boiling water, heating oil, frying eggs, and crisping crackers, accomplishing these tasks within a time frame ranging from 5 to 20 minutes. Notably, the solar cooker featuring the glass mirror reflector exhibited a superior thermal efficiency of 33.7%, surpassing the efficiency of the counterpart with the chrome sticker reflector, which registered an efficiency of 30.9%. These findings underscore the efficacy of the glass mirror reflector in harnessing solar energy for enhanced cooking performance within this solar cooker configuration.